Risk indicators associated with root caries in independently living older adults. (August 2016) - Hayes, Martina; Da Mata, Cristiane; Cole, Margaret; McKenna, Gerald; Burke, Francis; Allen, Patrick Finbarr
Abstract: Objective: To determine the risk indicators associated with root caries experience in a cohort of independently living older adults in Ireland. Methods: The data reported in the present study were obtained from a prospective longitudinal study conducted in a cohort of independently living older adults (n = 334). Each subject underwent an oral examination, performed by a single calibrated examiner, to determine the root caries index and other clinical variables. Questionnaires were used to collect data on oral hygiene habits, diet, smoking and alcohol habits and education level. A regression analysis with the outcome variable of root caries experience (no/yes) was conducted. Results: A total of 334 older dentate adults with a mean age of 69.1 years were examined. 53.3% had at least one filled or decayed root surface. The median root caries index was 3.13 (IQR 0.00, 13.92). The results from the multivariate regression analysis indicated that individuals with poor plaque control (OR 9.59, 95% CI 3.84–24.00), xerostomia (OR 18.49, 95% CI 2.00–172.80), two or more teeth with coronal decay (OR 4.50, 95% CI 2.02–10.02) and 37 or more exposed root surfaces (OR 5.48, 95% CI 2.49–12.01) were more likely to have been affected by root caries. Conclusions: The prevalence of root caries was high in this cohort. This study suggests a correlation between root caries and the variables poor plaque control, xerostomia, coronal decay (≥2 teeth affected) and exposed root surfaces (≥37). The significance of these risk indicators and the resulting prediction model should be further evaluated in a prospective study of root caries incidence. Clinical significance: Identification of risk indicators for root caries in independently living older adults would facilitate dental practitioners to identify those who would benefit most from interventions aimed at prevention.